Muscle pathology in juvenile dermatomyositis - Calore, Edenilson Eduardo (1997)
OBJECTIVE: To study muscle biopsies, using histochemistry, on ten children with infantile dermatomyositis. DESIGN: Series of ten patients (of whom eight patients had received treatment and two had not) were submitted to muscle biopsy in order to diagnose possible inflammatory myopathy or to detect recurrences. PLACE OF DEVELOPMENT OF THE STUDY: Public Health Service of São Paulo State. PARTICIPANTS: children with clinical features of inflammatory myopathy. INTERVENTION: biopsies were performed on the vastus lateralis using local anesthetic. Histochemistry was performed according to standardized methods. RESULTS: Architectural changes of the muscle fibers, necrosis of variable intensity and accentuated evidence of regeneration were observed in patients who had not received treatment (2 cases) and in one case where muscular weakness persisted in spite of corticosteroid therapy. Necrosis and regeneration were minimal or absent in cases treated for one year or more (4 cases). In 3 cases with clinical and laboratorial recurrences, muscle necrosis and architectural changes were detected. CONCLUSIONS: It was concluded that muscle biopsy could aid in diagnosing infantile dermatomyositis as well as in detecting recurrences even in cases without clinical activity of the disease.